2017
DOI: 10.1090/proc/13480
|View full text |Cite
|
Sign up to set email alerts
|

On the minimal number of singular fibers in Lefschetz fibrations over the torus

Abstract: Abstract. We show that the minimal number of singular fibers N (g, 1) in a genus-g Lefschetz fibration over the torus is at least 3. As an application, we show that N (g, 1) ∈ {3, 4} for g ≥ 5, N (g, 1) ∈ {3, 4, 5} for g = 3, 4 and N (2, 1) = 7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Remark 13. For g ≥ 3 and h = 1, 2 we find that genus-g Lefschetz fibrations over Σ h constructed in [19,17,29] are indecomposable and minimal. The minimality follows from the result of [27], and the indecomposability follows from the number of singular fibers and the lower bounds on the number of singular fibers of Lefschetz fibrations over S 2 (see [8]) and T 2 (see [29]).…”
Section: Positive Factorizations and Proofsmentioning
confidence: 89%
See 2 more Smart Citations
“…Remark 13. For g ≥ 3 and h = 1, 2 we find that genus-g Lefschetz fibrations over Σ h constructed in [19,17,29] are indecomposable and minimal. The minimality follows from the result of [27], and the indecomposability follows from the number of singular fibers and the lower bounds on the number of singular fibers of Lefschetz fibrations over S 2 (see [8]) and T 2 (see [29]).…”
Section: Positive Factorizations and Proofsmentioning
confidence: 89%
“…For g ≥ 3 and h = 1, 2 we find that genus-g Lefschetz fibrations over Σ h constructed in [19,17,29] are indecomposable and minimal. The minimality follows from the result of [27], and the indecomposability follows from the number of singular fibers and the lower bounds on the number of singular fibers of Lefschetz fibrations over S 2 (see [8]) and T 2 (see [29]). In [9], it was shown that a genus-g Lefschetz fibration over Σ h with a "maximal section" (see [9] for the definition) is indecomposable (as a fiber sum of two genus-g Lefschetz fibrations with a section) if h ≥ 1.…”
Section: Positive Factorizations and Proofsmentioning
confidence: 89%
See 1 more Smart Citation